PP-036 Stability study of 5 mg/ml oxybutynin oral suspension in syrspend. (14th February 2016) - Lesourd, F; Bellay, R; Quilliec, C; Lester, MA; Boivin, PN; Gicquel, T
Abstract : Background: Oxybutynin blocks the release of acetylcholine on the surface of the bladder's muscle. This drug has two indications: urinary incontinence and symptoms of detrusor muscle hyperactivity in the paediatric population. Oxybutynin is a common paediatric prescription but only commercially available in tablet form, which is unsuitable for paediatric use. We developed oral suspensions but information is not available on the stability of oxybutynin in this form. Purpose: The aim of this study was to evaluate the physicochemical stability of 5 mg/mL oxybutynin oral suspension in commercial compounding excipient Syrspend. Material and methods: An oral suspension was prepared using oxybutynin powder and Syrspend, packaged in amber vials, to protect from light, and stored at 25°C. Several parameters were studied on different days 0, 3, 5, 8, 10, 15, 30 and 60: microbiological stability (cultures at 36°C on agar), physical stability (macroscopic appearance, osmolality) and chemical stability (pH, concentration). We used a liquid chromatography high resolution mass spectrometer (Q Exactive ThermoFisherScientific). The chromatographic separation of the analytes was performed with an Accela pump equipped with a Thermo Fisher C18 Accucore column (100 × 2.1 mm, 2.6 μM). Data were acquired in targeted single ion monitoring (t-SIM) mode and quantification was performed by extracting the exact mass value of protonated oxybutynin (358.2376 m/z) using a 5 ppm mass window. Results: No culture growth was observed and macroscopic appearance was unchanged during the study period. Physical properties remained stable: pH (4.21–4.29) and osmolality (56–78 mOsm/L) during the 60 day period. The concentration of oxybutynin was 100.9% on day 8 and decreased significantly to 40.2% by day 30. Conclusion: These results indicate that microbiological stability and physical stability are acceptable but the concentration does not allow us to go beyond 8 days. Further study will be conducted to see whether the current findings can be replicated. References and/or Acknowledgements: European Pharmacopoeia No conflict of interest.